PENGARUH TOTAL PEMBIAYAAN, DANA PIHAK KETIGA (DPK), DAN NON-PERFOMING FINANCING (NPF) TERHADAP PROFITABILITAS (ROE) PT. BANK MUAMALAT INDONESIA TBK. PERIODE 2014-2024 - Putri, Diva Carrisa; Indrarini, Rachma (Universitas Negeri Surabaya, 2025)
Bank Muamalat as a growing Islamic bank, BMI faces challenges in increasing its profitability by as-sessing the effectiveness of equity management and identifying strategies that can improve financial performance. This study aims to analyze the effect of Total Financing, Third Party Funds (DPK), and Non-Performing Financing (NPF) on Profitability (Return on Equity / ROE) at PT Bank Muamalat Indo-nesia Tbk during the period 2014-2024. The research method used is associative quantitative, with secondary data in the form of quarterly financial reports of Bank Muamalat which are analyzed using Multiple Linear Regression through SPSS software. The results showed that Total Financing has a positive and significant effect on ROE, while DPK and NPF have a negative and significant effect on ROE. Simultaneously, Total Financing, DPK, and NPF have a significant effect on ROE. This finding confirms that an increase in financing can increase profitability, but high credit risk (NPF) and less than optimal DPK management can reduce the return on equity (ROE). Therefore, Bank Muamalat needs to optimize financing strategies, improve the efficiency of DPK management, and strengthen credit risk mitigation to increase profitability and competitiveness in the Islamic banking industry.